Pemetaan Densitas Larva Aedes Aegypti Berdasarkan Pemberantasan Sarang Nyamuk (PSN) di Kelurahan Paccerakkang dan Tamalanrea - Effendy, Thoeng Fenni C.; Ishak, Hasanuddin; Birawida, Agus Bintara (Hasanuddin Journal of Public Health, 2020)
Makassar City is one of the areas most at risk of Dengue Fever (DHF). One form of dengue prevention is to break the chain of transmission of mosquitoes, which is to prevent the breeding of mosquito vectors through efforts to eradicate mosquito nests (PSN). Mapping the density of aedes aegypti mosquitoes based on the behavior of eradicating mosquito nests (PSN) in Paccerakkang Village, Tamalanrea Village, Makassar City. This type of research is an observational survey with cross sectional method with descriptive analytic approach and using a questionnaire as an interview guide. The sample in this study was the house of DHF sufferers and houses within a radius of 100 meters from patients who were in Paccerakkang Village as many as 98 houses and Tamalanrea Village 61 houses were determined using purposive sampling method. The results of this study found that 39.8% of respondents' houses in Paccerakkang were found to be larvae and in Tamalanrea at 62.3%. 3M's behavior in both village is also incomplete and low, namely 14.3% and 13.1% respectively, while the use of bubate abate is 48% and 34.4%. Based on the Density Figure (DF) determined by WHO, the two villages are included in areas with Angka Bebas Jentik (ABJ) which have a high risk of DHF transmission.